2022
DOI: 10.1080/17425255.2022.2132931
|View full text |Cite
|
Sign up to set email alerts
|

Drug pharmacokinetics in the obese population: challenging common assumptions on predictors of obesity-related parameter changes

Abstract: Introduction:Obesity is associated with many physiological changes. We review available evidence regarding five commonly accepted assumptions to a priori predict the impact of obesity on drug pharmacokinetics (PK). Areas covered: The investigated assumptions are: 1) lean body weight is the preferred descriptor of clearance and dose adjustments; 2) volume of distribution increases for lipophilic, but not for hydrophilic drugs; 3) CYP-3A4 activity is suppressed and UGT activity is increased, implying decreased a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
47
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 26 publications
(47 citation statements)
references
References 141 publications
0
47
0
Order By: Relevance
“…However, until sufficient verification of PBPK modeling in obese subjects has been performed and confidence is sufficiently high in prospective predictions, PBPK modeling could be used to support initial dose estimates for clinical trials and also systematically elucidate the impact of key parameters among the (patho)physiological changes, drug properties, and longitudinal changes, which all interact with each other. 16,17 Any translational or clinical characterization of the effects of obesity on the PK of an investigational agent in development should be coupled with an assessment of anticipated clinical impact. This reinforces the critical importance of characterizing the exposure-response relationships for efficacy and safety throughout drug development.…”
Section: Clinical Pharmacology Tools To Evaluate Impact Of Obesity On...mentioning
confidence: 99%
See 1 more Smart Citation
“…However, until sufficient verification of PBPK modeling in obese subjects has been performed and confidence is sufficiently high in prospective predictions, PBPK modeling could be used to support initial dose estimates for clinical trials and also systematically elucidate the impact of key parameters among the (patho)physiological changes, drug properties, and longitudinal changes, which all interact with each other. 16,17 Any translational or clinical characterization of the effects of obesity on the PK of an investigational agent in development should be coupled with an assessment of anticipated clinical impact. This reinforces the critical importance of characterizing the exposure-response relationships for efficacy and safety throughout drug development.…”
Section: Clinical Pharmacology Tools To Evaluate Impact Of Obesity On...mentioning
confidence: 99%
“…Application of these models in an obese population has received increasing attention over the past few years due to their mechanistic nature. However, until sufficient verification of PBPK modeling in obese subjects has been performed and confidence is sufficiently high in prospective predictions, PBPK modeling could be used to support initial dose estimates for clinical trials and also systematically elucidate the impact of key parameters among the (patho)physiological changes, drug properties, and longitudinal changes, which all interact with each other 16,17 …”
Section: Clinical Pharmacology Tools To Evaluate Impact Of Obesity On...mentioning
confidence: 99%
“…This applies not only to clinical practice but also when designing clinical trials. Some studies have shown that proactively measuring infliximab trough levels and adjusting the dose independently of disease activity may not offer a benefit over conventional therapy (4,5). Those studies used infliximab concentrations that have historically been considered to correlate with better efficacy but perhaps the standardization of the goal drug concentration cannot really be applied to the entire population.…”
Section: Guarantormentioning
confidence: 99%
“…In these analyses, it is crucial to use a data-driven approach that avoids preconceived notions. It could consider multiple size descriptors, in conjunction with other patient and treatment characteristics, using both linear and nonlinear functions (4).…”
Section: Guarantormentioning
confidence: 99%
“…8,21 As a result, the Vd is typically larger compared with less lipophilic drugs; however, there is wide variation. 8,18,21,22 Obesity can also alter the pharmacokinetics of lipophilic drugs through their accumulation in adipose tissue. 21 This increased Vd of lipophilic drugs in people with obesity can decrease the initial/maximum concentration of a drug.…”
Section: What Is the Role Of The Therapeutic Window Of A Drug For Inf...mentioning
confidence: 99%